Connections, rituals and identities: healthcare students' descriptions of objects that represent resilience. Issue 3 (28th December 2021) - Maddock, Angela; Oates, Jennifer
Abstract : Purpose: Health-care student resilience is a well-researched topic, although the concept continues to evolve, not least as "resilience-building" has become an expected feature of health-care student professional education. The study aimed to understand the concept of resilience from the point of view of student nurses and midwives. Design/methodology/approach: The study used a novel arts-informed method, informed by Miller's and Turkle's work on "evocative objects." A total of 25 student nurses and midwives from a London-based university selected "resilience objects" which were photographed and discussed during interviews with an artist-researcher. Findings: Analysis of the interviews revealed that "resilience" was founded on identity, connection, activity and protection. "Resilience objects" were used in everyday rituals and "resilience" was a characteristic that developed over time through the inhabiting of multiple identities. Practical implications: Given that resilience is intertwined with notions of identity, health-care faculties should enhance students' sense of identity, including, but not exclusively, nursing or midwifery professional identity, and invite students to develop simple rituals to cope with the challenges of health-care work. Originality/value: To the best of the authors' knowledge, this is the first study to locate health-care students' resilience in specific material objects. Novel insights are that health-care students used everyday rituals and everyday objects to connect to their sense of purpose and manage their emotions, as means of being resilient.